Rice microRNA osa‐miR1848 targets the obtusifoliol 14α‐demethylase gene OsCYP51G3 and mediates the biosynthesis of phytosterols and brassinosteroids during development and in response to stress. Issue 3 (17th June 2015) - Xia, Kuaifei; Ou, Xiaojing; Tang, Huadan; Wang, Ren; Wu, Ping; Jia, Yongxia; Wei, Xiaoyi; Xu, Xinlan; Kang, Seung‐Hye; Kim, Seong‐Ki; Zhang, Mingyong
Summary: Phytosterols are membrane components or precursors for brassinosteroid (BR) biosynthesis. As they cannot be transported long distances, their homeostasis is tightly controlled through their biosynthesis and metabolism. However, it is unknown whether microRNAs are involved in their homeostatic regulation. Rice ( Oryza sativa ) plants transformed with microRNA osa‐miR1848 and its target, the obtusifoliol 14α‐demethylase gene, OsCYP51G3, were used to investigate the role of osa‐miR1848 in the regulation of phytosterol biosynthesis. osa‐miR1848 directs OsCYP51G3 mRNA cleavage to regulate phytosterol and BR biosynthesis in rice. The role of OsCYP51G3 as one of the osa‐miR1848 targets is supported by the opposite expression patterns of osa‐miR1848 and OsCYP51G3 in transgenic rice plants, and by the identification of OsCYP51G3 mRNA cleavage sites. Increased osa‐miR1848 and decreased OsCYP51G3 expression reduced phytosterol and BR concentrations, and caused typical phenotypic changes related to phytosterol and BR deficiency, including dwarf plants, erect leaves, semi‐sterile pollen grains, and shorter cells. Circadian expression of osa‐miR1848 regulated the diurnal abundance of OsCYP51G3 transcript in developing organs, and the response of OsCYP51G3 to salt stress. We propose that osa‐miR1848 regulates OsCYP51G3 expression posttranscriptionally, and mediates phytosterol and BR biosynthesis. osa‐miR1848 and OsCYP51G3 might have potential applications in rice breeding to modulate leaf angle, and the size and quality of seeds.